Analysis of an Inherited Dysfibrinogenemia Pedigree Associated with a Heterozygous Mutation in the FGA Gene - Li, Shaoxi; Wang, Mingshan; Li, Xiaolong; Xu, Qiyu; Liu, Siqi; Luo, Shasha; Chen, Yi (Hämostaseologie, 2020)
Objective This article aims to analyze the phenotype and genotype of an inherited dysfibrinogenemia pedigree associated with a heterozygous mutation in the FGA gene, and to investigate the pathogenesis of this disease.Clinical Presentation The proband of interest is a 29-year-old woman. She was in her 37 weeks of gestation. Routine coagulation tests showed low fibrinogen activity (0.91 g/L; normal range: 2.0–4.0 g/L) and normal fibrinogen antigen (FIB:Ag) level (2.09 g/L; normal range: 2.0–4.0 g/L).Techniques The prothrombin time, activated partial thromboplastin time, thrombin time, and activity of plasma fibrinogen (FIB:C) were detected by the one-stage clotting method. The FIB:Ag, D-dimer, and fibrinogen degradation products were tested by the immunoturbidimetry method. To identify the novel missense mutation, fibrinogen gene sequencing and molecular modeling were performed. We used ClustalX-2.1-win and online bioinformatic software to analyze the conservation and possible effect of the amino acid substitution on fibrinogen.Results Phenotypic analysis revealed that the FIB:C of the proband was significantly reduced while the FIB:Ag was normal. Sequencing analysis detected a heterozygous C.2185G > A point mutation in the FGA gene (AαGlu710Lys). Bioinformatic and modeling analyses indicated that the mutation probably caused harmful effects on fibrinogen.Conclusion The heterozygous mutation of Glu710Lys in the FGA gene was identified that could cause the reduction of the FIB structure stability and result in the dysfibrinogenemia.
Keywords: fibrinogen; dysfibrinogenemia; FGA; novel mutation